TINGKAT BAHAYA BENCANA TANAH LONGSOR DI KECAMATAN PANGKALAN KABUPATEN LIMAPULUH KOTA MENGGUNAKAN ANALISIS BIVARIAT - Ainul Karim; Ahyuni ahyuni (JURNAL BUANA, 2022)
Statistical analysis assessment of landslide susceptibility has become one of the topics of research that is currently developing. Several types of parameters are thought to be the factors responsible for the occurrence of ground movement. However, some data types and models are specific and cannot be implemented in different locations. What's more, the data stored in some parameters is divided into several classes, depending on the goals and vision of the researcher. This study presents a step in identifying the best variables to find the level of vulnerability to landslides using bivariate techniques (Weight of Evidence, WoE). The location of this research is an area prone to landslides which cause a lot of losses, so this research is expected to be a material consideration for interested parties.